Has AMS-02 observed two-component dark matter?. (4th December 2020) - Profumo, Stefano; Queiroz, Farinaldo; Siqueira, Clarissa
Abstract: There is convincing observational evidence for an increasing cosmic-ray positron-to-electron ratio at energies larger than ∼10 GeV, at odds with expectations from secondary positron production. The most recent AMS-02 data exhibit an interesting spectral feature consisting of a bump at an energy around 300 GeV followed by a drop around ∼800 GeV. A possible explanation for the most recent data is that the excess positron flux originates from decaying dark matter. Here, we show that models consisting of two dark matter particle species contributing equally to the global cosmological dark matter density provide good fits to the data. The favored models, with a best-fit with χ 2 / d . o . f ∼ 2, consist of a first species weighing 750 GeV decaying with a lifetime τ χ ∼ 10 26 s to τ lepton pairs (or to a pair of vector bosons subsequently decaying to a τ pair each), and a second species with a mass around 2.3 TeV decaying to μ lepton pairs. We provide a few possible concrete realizations for this scenario.